Waypoint navigation of quad-rotor MAV using Fuzzy-PID control - Goh, Ming Qian; Pebrianti, Dwi; Bayuaji, Luhur; Nor Rul Hasma, Abdullah; Mahfuzah, Mustafa; Mohammad, Syafrullah; Indra, Riyanto (Springer Singapore, 2018)
Quad-rotor Micro Aerial Vehicle (MAV) is a multi-rotor MAV with four propellers which propel the MAV up to the air and move around. It has high maneuverability to move around, such as roll, pitch and yaw movements. However, line of sight and radio control effective range are the major limitation for the MAVs which significantly shorten the travel distance. Therefore, we proposed a waypoint navigation quad-rotor MAV based on Fuzzy-PID controller in this paper. User can set mission with multiple waypoint and the Fuzzy-PID controller will control MAV autonomously moving along the waypoint to the desired position without remotely controlled by radio control and guidance of pilot. The results show Fuzzy-PID controller is capable to control MAV to move to the desired position with high accuracy. As the conclusion, Fuzzy-PID controller is successfully designed for waypoint navigation in quad-rotor MAV. The result shows that the overshoot percentage (%OS) of the designed Fuzzy-PID controller for x position is 2.17% while y position is 0.93%. Additionally, the steady-state error for x position and y position are 0.54% and 0.56% respectively. Therefore, the performance of Fuzzy-PID controller is better than PID controller.